Proceedings of 2nd International Multi-Disciplinary Conference Theme: Integrated Sciences and Technologies, IMDC-IST 2021, 7-9 2022
DOI: 10.4108/eai.7-9-2021.2314874
|View full text |Cite
|
Sign up to set email alerts
|

A New Version of Modified Camel Algorithm for Engineering Applications

Abstract: The new modified camel algorithm (NMCA) is presented as a novel optimization method for tackling optimization problems in this research. The modified camel algorithm (MCA) and other metaheuristic algorithms are not the same as NMCA.Where it offers a fresh perspective on global optimization. The suggested method is validated using power distribution system challenges (engineering problems) that are frequently encountered in the optimization field. The IEEE 69-and 33-bus systems were used in the simulations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The structure of the modified camel algorithm MCTA that mimics camels travelling behavior is easy because there are less setting parameters than in the old one. In order to implement the MCTA, it is suggested that N camels (the Camel Caravan) move through a (D)-dimensional environment of camels, and it is shown that the flow is (π‘₯ 𝑖,π‘–π‘‘π‘Ÿ ) which represents the location of the camel (i) at time iteration (itr) [28,29].…”
Section: Modified Camel Traveling Algorithmmentioning
confidence: 99%
“…The structure of the modified camel algorithm MCTA that mimics camels travelling behavior is easy because there are less setting parameters than in the old one. In order to implement the MCTA, it is suggested that N camels (the Camel Caravan) move through a (D)-dimensional environment of camels, and it is shown that the flow is (π‘₯ 𝑖,π‘–π‘‘π‘Ÿ ) which represents the location of the camel (i) at time iteration (itr) [28,29].…”
Section: Modified Camel Traveling Algorithmmentioning
confidence: 99%